Steganography and Cryptography Techniques Based Secure Data Transferring Through Public Network Channel (Baghdad Science Journal, 2022)
Attacking a transferred data over a network is frequently happened millions time a day. To address this problem, a secure scheme is proposed which is securing a transferred data over a network. The proposed scheme uses two techniques to guarantee a secure transferring for a message. The message is encrypted as a first step, and then it is hided in a video cover.  The proposed encrypting technique is RC4 stream cipher algorithm in order to increase the message's confidentiality, as well as improving the least significant bit embedding algorithm (LSB) by adding an additional layer of security. The improvement of the LSB method comes by replacing the adopted sequential selection by a random selection manner of the frames and the pixels with two secret random keys. Therefore, the hidden message remains protected even if the stego-object is hacked because the attacker is unable to know the correct frames and pixels that hold each bit of the secret message in addition to difficulty to successfully rebuild the message. The results refer to that the proposed scheme provides a good performance for evaluation metric that is used in this purpose when compared to a large number of related previous methods.